Design and Optimization of Elliptical Cavity Tube Receivers in the Parabolic Trough Solar Collector - Fei Cao; Lei Wang; Tianyu Zhu (International Journal of Photoenergy)
The nonfragile cavity receiver is of high significance to the solar parabolic trough collector (PTC). In the present study, light distributions in the cavity under different tracking error angles and PTC configurations are analyzed. A new elliptical cavity geometry is proposed and analyzed. It is obtained from this study that light distribution on the tube receiver is asymmetrical when tracking error occurs. On increasing the tracking error angle, more lights are sheltered by the cavity outer surface. The PTC focal distance has negative correlation with the cavity open length, whereas the PTC concentration ratio has positive correlation with the cavity open length. Increasing the tracking error angle and increasing the PTC focal distance would both decrease the cavity blackness. Introducing a flat plate reflector at the elliptical cavity open inlet can largely increase the cavity darkness.